2018
DOI: 10.1016/j.rmed.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Safety of tiotropium/olodaterol in chronic obstructive pulmonary disease: pooled analysis of three large, 52-week, randomized clinical trials

Abstract: clinicaltrials. gov (TONADO 1 and 2: NCT01431274, NCT01431287; DYNAGITO: NCT02296138).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
1
25
1
1
Order By: Relevance
“…The safety data show a slightly higher proportion of patients with adverse events in the tiotropium/olodaterol period compared with the tiotropium period, but this was a small population and a relatively short trial. A large safety database of longer-term and larger trials has shown that there is no difference between tiotropium/olodaterol and tiotropium in the proportion of patients with adverse events [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…The safety data show a slightly higher proportion of patients with adverse events in the tiotropium/olodaterol period compared with the tiotropium period, but this was a small population and a relatively short trial. A large safety database of longer-term and larger trials has shown that there is no difference between tiotropium/olodaterol and tiotropium in the proportion of patients with adverse events [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Safety data from the pooled population have been published previously [18]. In brief, the proportion of patients discontinuing treatment was lower with tiotropium/olodaterol (12.5%) compared with tiotropium (16.4%).…”
Section: Safetymentioning
confidence: 95%
“…In a pooled analysis of data from three 52-week trials (TOnado 1 and 2 and DYNAGITO), the rate of AEs per 100 patient-years (PY) was 152.66 with tiotropium/olodaterol and 158.33 with tiotropium (exposure-adjusted RR 0.96; 95% CI 0.92–1.01) [34]. There were 22.16 and 24.22 SAEs per 100 PY with tiotropium/olodaterol and tiotropium (RR 0.91; 95% CI 0.84–1.00).…”
Section: Tolerability Of Tiotropium/olodaterolmentioning
confidence: 99%